The Effect of Nutrition Education Using Audio Visual on Knowledge and Attitudes of Obesity Prevention in Adolescents at Muhammadiyah 3 Middle School Samarinda - Fadhilla Nurhaditsa; Supriadi B; Rieska Indah Mulyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Obesity is a world health case that has been declared a world epidemic case by the World Health Organization (WHO) which requires immediate treatment. Providing nutritional education is one way to overcome this. This research aims to determine the effect of nutrition education using audio-visual on knowledge and attitudes towards obesity prevention in adolescents at SMP Muhammadiyah 3 Samarinda. This research is a pre-experimental design research with a one group pretest-posttest design approach. The results of this research show that there is an influence of nutrition education using audio-visuals on knowledge and attitudes with a p value of 0.000 (p < 0.05). There is an influence of providing nutrition education using audio-visual media on knowledge and attitudes towards preventing obesity in adolescents at SMP Muhammadiyah 3 Samarinda.